EFFECT OF BLOOD TRANSFUSION ON CLINICO-BIOCHEMICAL PARAMETERS IN ANAEMIC PUPS - Kumar, Anil; Kumar, Rajesh (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
A total of 25 clinically anaemic pups aged 3-5 months were randomly divided into 5 equal groups. Pups in Group T5 were treated with single i/m injection of iron dextran and served as control group. Pups in Group T1 were transfused with fresh blood and those of Group T2, T3, and T4 received 7, 14 and 21 days preserved (4-6oC) blood, respectively, @ 20 ml/kg body weight as a single therapy. The clinico-biochemical parameters before blood transfusion showed significant increase in pulse and respiration rates, and significant decrease in total protein, albumin and blood glucose concentration. After 24, 72 and 120 hrs of blood transfusion, a significant improvement in the clinico biochemical parameters approaching to normal values was observed, whereas no significant change was noticed in anemic control group treated with single i/m injection of iron dextran. It was concluded that blood transfusion, irrespective of fresh or stored blood, can improve clinico biochemical status and thus is considered as an important life saving measure in severely anemic dogs.
Keywords: Anaemia; Anorexia; Pups; Blood transfusion; Biochemical profile; Clinical status